Bis(terpyridine) Ru(iii) complex functionalized porous polycarbazole for visible-light driven chemical reactions. Issue 31 (22nd July 2021) - Anito, Dejene Assefa; Wang, Tian-Xiong; Liang, Hai-Peng; Ding, Xuesong; Han, Bao-Hang
Abstract : Bis(terpyridine)Ru(iii ) complex functionalized porous polycarbazole for photocatalytic amine coupling, aerobic hydroxylation of arylboronic acids, and selective oxidation of sulfides. Abstract : The transformation of organic molecules into compounds of interest by the utilization of solar energy is an innovative approach that is attracting a lot of attention from material scientists. Introducing potent chelation sites onto a porous matrix is imperative for the purpose of effectively recycling cost-prohibitive catalysts, e.g., ruthenium and iridium complexes. To this end, bis(terpyridine) Ru(iii ) complex functionalized porous polycarbazoles, CPOP-32-Ru and CPOP-32-Ru′, were synthesized. Both polymers showed high thermal stability and efficient photocatalytic activities toward a range of important organic transformations, including amine coupling, aerobic hydroxylation of arylboronic acids, and selective oxidation of sulfides.